Diagnostic Potential of Recombinant scFv Antibodies Generated Against Hemagglutinin Protein of Influenza A Virus - Rajput, Roopali; Sharma, Gaurav; Rawat, Varsha; Gautam, Anju; Kumar, Binod; Pattnaik, B.; Pradhan, H. K.; Khanna, Madhu (Frontiers in Immunology, 2015)
Human influenza A viruses have been the cause of enormous socio-economic losses worldwide. In order to combat such a notorious pathogen, hemagglutinin protein (HA) has been a preferred target for generation of neutralizing-antibodies, as potent therapeutic/ diagnostic agents. In the present study, recombinant anti-HA single chain variable fragment (scFv) antibodies were constructed using the phage display technology to aid in diagnosis and treatment of human influenza A virus infections. Spleen cells of mice hyper-immunized with A/New Caledonia/20/99 (H1N1) virus were used as the source for recombinant antibody (rAb) production. The antigen-binding phages were quantified after 6 rounds of bio-panning against A/New Caledonia/20/99 (H1N1), A/California/07/2009 (H1N1)-like, or A/Udorn/307/72(H3N2) viruses. The phage yield was maximum for the A/New Caledonia/20/99 (H1N1), however, considerable cross-reactivity was observed for the other virus strains as well. The HA-specific polyclonal rAb preparation was subjected to selection of single clones for identification of high reactive relatively conserved epitopes. The high affinity rAbs were tested against certain known conserved HA epitopes by peptide ELISA. Three recombinant mAbs showed reactivity with both the H1N1 strains and one (C5) showed binding with all the three viral strains. The C5 antibody was thus used for development of an ELISA test for diagnosis of influenza virus infection. Based on the sample size in the current analysis, the ELISA test demonstrated 83.9% sensitivity and 100% specificity. Thus, the ELISA, developed in our study, may prove as a cheaper alternative to the presently used real time RT-PCR test for detection of human influenza A viruses in clinical specimens, which will be beneficial, especially in the developing countries. Since, the two antibodies identified in this study are reactive to conserved HA epitopes; these may prove as potential therapeutic agents as well.